1982
DOI: 10.1073/pnas.79.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and the encoded amino acids of human serum albumin mRNA.

Abstract: The complete nucleotide sequence of human serum albumin mRNA has been determined from recombinant cDNA clones and from a primer-extended cDNA synthesis on the mRNA template. The sequence is composed of 2078 nucleotides, starting upstream from a potential ribosome binding site in the 5' untranslated region. It contains all the translated codons and extends into the poly(A) at the 3' terminus. Part of the translated sequence codes for a hydrophobic prepeptide, Met-Lys-Trp-ValThr-Phe-Ile-Ser-Leu-Leu-Phe-Leu-Phe-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(119 citation statements)
references
References 17 publications
4
114
0
1
Order By: Relevance
“…MDA levels were also elevated in β-TM patients (median [IQR], 30 nmol/ ml) with a range of 10-112 nmol/ml compared with the control group (median [IQR], 10 [7][8][9][10][11][12][13][14][15] nmol/ml; range 5-18 nmol/ml); p < 0.001 (Table 1 and Figure 1).…”
Section: Levels Of Ima and Mda In Patients With β-Tm And Healthy Contmentioning
confidence: 93%
See 1 more Smart Citation
“…MDA levels were also elevated in β-TM patients (median [IQR], 30 nmol/ ml) with a range of 10-112 nmol/ml compared with the control group (median [IQR], 10 [7][8][9][10][11][12][13][14][15] nmol/ml; range 5-18 nmol/ml); p < 0.001 (Table 1 and Figure 1).…”
Section: Levels Of Ima and Mda In Patients With β-Tm And Healthy Contmentioning
confidence: 93%
“…Human serum albumin (HSA) is composed of 585 amino acids (66,438 Da), containing 17 pairs of intra-molecular disulfide bridges and one free cysteine (Cys34) [9]. HSA has the unique capability of binding reversibly or covalently to a wide diversity of ligands including water, cations (such as Ca 2+ , Na + and K + ), fatty acids, hormones, bilirubin and drugs [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 1975 the amino acid sequences of bovine (Brown, 1975) and human (Behrens et al, 1975;Meloun et al, 1975) albumins were reported. Since that time, the cDNA sequence, and thus the inferred amino acid sequence, has been determined for the following vertebrate albumins: human (Lawn et al, 1981;Dugaiczyk et al, 1982), rat (Sargent et al, 1981b), mouse (Minghetti et al, 1985), pig (Weinstock & Baldwin, 1988), sheep (Brown et al, 1989), frog (Haefliger et al, 1989), and salmon (Byrnes & Gannon, 1990). The most characteristic feature of the albumin sequence is the repetitious pattern of 17 disulfide bridges that organizes the molecule into three homologous, yet distinct, domains.…”
mentioning
confidence: 99%
“…First, a large number of proteins are known to be proteolyzed within the endomembrane system, at sites separate from signal peptidase cleavage. These include the endoproteolytic processing of, for example, proalbumin (Dugaiczyk et al, 1982), proinsulin (Nolan et al, 1971), interleukin 3 (Fung et al, 1984;Yokota et al, 1984), prosomatostatin (Benoit et al, 1988;Lepage-Lezin et al, 1991 ;Goodman et al, 1983), prodynorphin (Devi et al, 1989;Civelli et al, 1985), and the procorticotropidendorphin precursor (Schnabel et al, 1989). These cleavages occur on either side of dibasic pairs of amino acids, such as Arg-Arg or Lys-Arg, or on the COOH- (Benoit et al, 1988;Fung et al, 1984) or NH,-terminal side (Devi et al, 1989;Civelli et al, 1985) of monobasic residues, usually Arg, in a number of processed proteins.…”
mentioning
confidence: 99%